2018
DOI: 10.2147/ijgm.s171387
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of primary colorectal follicular lymphoma and multiple myeloma: a case report

Abstract: Colorectal follicular lymphoma (FL) occurs less frequently than duodenal-type FL, which is an established entity, and primary multiple FL only involving the colon is rare. Furthermore, the coexistence of lymphoma and multiple myeloma (MM) within the same patient is rare and the current study reports such a case. The patient was an asymptomatic 62-year-old man. He underwent colonoscopy screening, which revealed at least five polypoid tumors from the cecum to the rectum. Biopsy samples stained positive for CD20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, only one case of FL has been reported. The reason for the merging with MM is unknown; i.e., it is unknown whether it is derived from FL, and it is unknown whether activated CD4 T-cells were involved [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, only one case of FL has been reported. The reason for the merging with MM is unknown; i.e., it is unknown whether it is derived from FL, and it is unknown whether activated CD4 T-cells were involved [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of venetoclax, however, was limited in the treatment of follicular lymphoma [ 16 , 17 ]. In a report of FL complicated with MM, rituximab and bendamustine were administered for the treatment of FL, followed by lenalidomide and dexamethasone for the treatment of MM [ 4 ]. Although the BCL2 protein was not analyzed, lenalidomide was a useful treatment option for both FL and MM [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age was 65.8 (range: 56-75) years old, and the male-to-female ratio was 4:4. According to the Lugano classification, the ratio of clinical stages I:II1 was 6: 2 and the endoscopic appearances of papular, polypoid and flat elevated type were observed in 4, 2 and 2cases, respectively (7)(8)(9)(10)(11)(12)(13)(14), and all of which showed raised lesions (Table). Nakamura et al reported that the endoscopic features of intestinal lymphoma may be classified as polypoid, ulcerative, multiple lymphomatous polyposis (MLP), diffuse, and mixed type (15).…”
Section: Discussionmentioning
confidence: 99%
“…B-cell lymphoma and MM rarely occur simultaneously or in succession. We reviewed similar cases from the PubMed database and found that the types of B-cell lymphoma coexisting with MM were Hodgkin's lymphoma, [ 12 , 13 ] chronic lymphocytic leukemia/small lymphocytic lymphoma, [ 14 , 15 ] diffuse large B-cell lymphoma, [ 16 ] follicular lymphoma [ 17 ] and mantle cell lymphoma. [ 18 ] The most common type was chronic lymphocytic leukemia/small lymphocytic lymphoma.…”
Section: Case Presentationmentioning
confidence: 99%